(untitled) (Al-NASR, 2025)
The Holy Quran is such a great book that has the honor of being the inspired word of Allah Almighty. Reading it brings reward and acting upon it brings salvation. But in order to act upon it, it is necessary to have a correct understanding of this book. And for its correct understanding, knowledge of the sciences related to it is very important. One of the means of understanding the Quran is also the interpretation of the Quran, through which one can gain access to the secrets and symbols hidden in it by knowing them. In each era, commentators wrote interpretations according to their special taste and focus. Due to which the scope of interpretation and Quranic sciences continued to expand. If we look at the interpretations of the scholars of the second century, they will only be seen to contain the sayings of the companions and followers, but after that, the sciences of interpretation only increase in each era. The principles of interpretation hold a special place in the interpretation of the Quran. It is very important for a teacher teaching the Quran to be well aware of the principles of interpretation because the Quran is a comprehensive text. It is very important to know all these principles for its interpretation. Which have been determined by the scholars of the nation. Sheikh Islam Imam Ibn Taymiyyah’s "Introduction to the Principles of Interpretation" and Shah Waliullah’s book "Al-Fawz Al-Kabir" are very important books regarding the principles of interpretation.